Synchrony in Vegetative and Reproductive Characters and its Impact on Yield Performance of Rice (Bangladesh Journal of Genetics and Biotechnology, 2009)
Key words: Rice, mean, coefficient of variation synchrony, tillering Bangladesh j. genet. biotechnol. 7(1&2): 1-4 2006 (June & December)